A new species of Brachionidium (Pleurothallidinae: Orchidaceae) from the high montane forest in the Central Jungle of Peru - Valenzuela Gamarra, Luis (Universidad de Costa Rica, 2017)
A new species of Brachionidium was found on the highest mountains of the Central Jungle of Peru, on a wet Puna forest at 3470 m altitude. This species is similar to B. loxense and B. diaphanum but can be distinguished by its elliptic leaves with petioles 3–4 mm long; the short erect floral peduncle 2–3 mm long; the pink translucent sepals, red-wine toward the base; the floral bract spatuliform 15 × 5 mm; lip red-wine, bimarginated, trapezoidal, small, fleshy, obtuse acuminate, slightly prolonged lateral lobes antrorse and straight with a strongly pubescent cordate callus, split towards the apex.